Salas de recursos multifuncionais: a interação entre família e escola no Município de Matelândia - Paraná - Silva, Josiane Marcela Andrade (2018)
This research aims to understand and analyze if there is a participation and also the way it occurs the family interaction in education policy, specifity of multifunctional classes which help the special education students in the perspective of inclusive education at the public education network in Matelândia – Paraná. In order to reaching the study objective, there were specific goals: Identify the family engagement and comprehension about the learning disability of the child; Understand the performance of the inclusive education policy worldwide and in Matelândia-PR; Check the teachers’ understanding about the family interaction to the student learning process; Apprehend the conception of inclusive education in the current legislation which implant the multifunctional classes; Comprehend and discuss the family into the inclusive education policy. In this regard, the question which directed the investigation was this one: In the face of the child educational needs of the target audience in the national policy of special education and the inclusive education perspective, how does the interaction between school and family happen? That way, it was necessary specific methodological procedures, defining it as qualitative, descriptive and exploratory research.During the documental research, they prioritized the federal, state and city legislation which treat about inclusive education.The bibliography subsidized a debate about the social policies and among them, the educational policy in the inclusive perspective and the family in the context of the social policies. The field researchcontemplated nine individuals, and among them, commom teachers, special education students’ families and multifunctional class teachers. The current investigation looks back the history of assisting people with disabilities in Brazil, special education progress to the inclusive perspective and also social policies in the specifity of education and family participation. On the basis of this study, it can be stated that there are weaknesses in the interaction among family, school and professionals who assist people with disabilities, development disordersand high levelskills. The main result of the researchwas the occurrence of communication between school and family, but not as desired, it needs to be improved. It will also be necessary to build strategies with the family and school in order to ease reliable and friendly environment for the children, the members of the family and the education professionals.